Study on the temporal and spatial distribution of Culex mosquitoes in Hanoi, Vietnam - Krambrich, J.; Thang Nguyen-Tien; Long Pham-Thanh; Sinh Dang-Xuan; Andersson, E.; Höller, P.; Duoc Trong Vu; Son Hai Tran; Lieu Thi Vu; Akaberi, D.; Ling, J.; Pettersson, J.H.-O.; et al. (Nature Portfolio, 2024)
Arboviruses transmitted by mosquitoes, including Japanese encephalitis virus (JEV), present a substantial global health threat. JEV is transmitted by mosquitoes in the genus Culex, which are common in both urban and rural areas in Vietnam. In 2020, we conducted a 1-year survey of Culex mosquito abundance in urban, suburban, and peri-urban areas of Hanoi using CDC-light traps. Mosquitoes were identified to species and sorted into pools based on species, sex, and trap location. The mosquito pools were also investigated by RT-qPCR for detection of JEV. In total, 4829 mosquitoes were collected over a total of 455 trap-nights, across 13 months. Collected mosquitoes included Culex, Aedes, Anopheles, and Mansonia species. Culex mosquitoes, primarily Cx. quinquefasciatus, predominated, especially in peri-urban areas. Most Culex mosquitoes were caught in the early months of the year. The distribution and abundance of mosquitoes exhibited variations across urban, suburban, and peri-urban sites, emphasizing the influence of environmental factors such as degree of urbanization, temperature and humidity on Culex abundance. No JEV was detected in the mosquito pools. This study establishes baseline knowledge of Culex abundance and temporal variation, which is crucial for understanding the potential for JEV transmission in Hanoi.